The importance of a Specialized Outpatient Clinic of Liaison Psychiatry in the Follow-Up of Patients with Heart Failure - Martins, Sofia; Ribeiro, Ângela; Mendes, Daniela; Ribeiro, Bruno (Acta Médica Portuguesa, 2022)
N/a.